Strategi Peningkatan Penjualan Kendaraan Bekas dengan Analisis SWOT - Widowati, Imas; Michelle Ratulangi; Daisy Ade Riany; Sutardjo (Jurnal Teknologika, 2025)
Marketing strategy is an important activity to carry out in order to achieve sales targets or by seeking a wage or profit advantage. This research aims to analyze and determine marketing strategies to increase sales of used cars and motorbikes at PT. UC Auction (Carsome). Data collection methods in this research are observation, interviews and literature as well as identification of internal and external factors, SWOT analysis with the SWOT matrix. The type of research methodology used is a qualitative descriptive method. The findings from this research show tha there are internal and exsternal factors in used cars and motorbike marketing strategy. PT. UC Auction (Carsome), that in 2023 sales of used cars and motorbike from PT. UC Auction (carsome) is still not optimal, this because the are more competitors selling the same vehicles. We recommend that PT. UC Auction (Carsome) is increasing digital marketing to keep up with the development of increasingly broad and modern marketing strategies